PENGARUH PRICE EARNING RATIO, EARNING PER SHARE, RETURN ON EQUITY, DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM (Pada Sektor Property and Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2017) - Mohamad Zulman Hakim; Dirvi Surya Abbas (Universitas Muhammadiyah Tangerang, 2019)
The purpose of this study was to determine the extent of the effect of price earnings ratio, earnings per share, return on equity, debt to equity ratio and net profit margin on stock returns. Price earning ratio is measured by the price per share divided by net income per share, earning per share is measured by net income after tax divided by the number of shares outstanding, as well as return on equity measured by net profit after tax divided by shareholders' equity multiplied by 100% , the debt to equity ratio is measured by total debt divided by total equity and net profit margin is measured by net income after tax divided by net sales income. The stock return as the dependent variable is measured by the closing price of the current year minus the closing price of the previous year's share and then divided by the closing price of the previous year.This study uses a sample of property and real estate subsector companies during 2013 - 2017 using purposive sampling method. The data used is obtained from annual reports listed on the Indonesia Stock Exchange. There were 17 companies during 2013-2017 that met the criteria. The analytical method used in this study is panel data regression analysis.The results of this study indicate that price earnings ratio, earnings per share, debt to equity ratio and net profit margin have no significant effect on stock returns. While return on equity has a significant positive effect on stock returns.Keywords: Price Earning Ratio, Earning per Share, Return on Equity, Debt to Equity Ratio, Net Profit Margin and Return Saham